Evaluation of the Fatigue behavior for the polymer matrix composite and hybrid composite - Najam, Abdul Rahman (Nahrain University College of Engineering Journal, 2011)
The characteristics of polymer materials which are containing ceramic particles has been investigated to find the information and data to give good expectation for composite behavior under fatigue damage. In this research epoxy resin reinforced by ceramic particles (Alumina, silicon carbide and graphite), withreinforcement particles size range between 36 and 45 Micrometer and 1 to 10 micrometer for graphite. The structure has been investigated under stress-strain and fatigue damage to evaluate the bound strength between the matrix and reinforcement phase. This examinations lead to discover new Techniques which isapplied during preparation of the composite materials. Basically this methodology will reduce the porosity which develops during mixing and solidification process, as a result /the bound strength between the polymer and the reinforcement will increase in another word the properties of the composite improve.The fatigue damage in the composites is complex because, it is combine between several damages, first matrix cracking and second debonding of the particles. The fatigue damage shows that pure epoxy give initial stress (26.2) MPa and its final failure is at 221 hundred thousand cycles in which the stress indicated is to be equal to 20 MPa. for the composite contain epoxy with aluminand slicon carbide, the initial stress is equal to (32.2) MPa and its final failure is at 910hundred thousand cycles in which the stress indicated is to be equal to 23 MPa. In the case of graphite reinforcement it is clear there is reduction in the value of maximum stress. The microstructure examination shows that the cracks stop at the reinforcement particles or goes around them. Crack propagation isthereby inhibited. This means that the fracture toughness of the composite increased